Ferrite shielding thickness and its effect on electromagnetic parameters in wireless power transfer for electric vehicles (EVs) - Ankur Yadav; Tushar Kanti Bera (Journal of Engineering and Applied Science, 2023)
Abstract Wireless power transfer (WPT) has become an increasingly popular technology for charging electronic devices wirelessly. One of the key challenges in WPT is increasing efficiency and reducing different losses in coils caused by the higher air gap and coil coupling between the primary and secondary coils. Ferrite shielding is a common technique used to reduce losses and increase the coupling in WPT systems. In this paper, we present an analysis and comparison study of the effect of ferrite shielding thickness ( $$F_T$$ F T ) on the electromagnetic parameters of WPT systems. We investigate the impact of varying the ferrite shielding thickness on parameters such as power transfer efficiency, coupling coefficient (k), and magnetic field strength (B). Our results show that increasing the ferrite shielding thickness can significantly reduce losses and improve the performance of WPT systems. Also, analyze the trade-off between ferrite shielding thickness and power transfer efficiency and provide guidelines for selecting an optimal thickness for a given application. This study provides valuable insights into the design and optimization with weight vs. coupling comparison for WPT systems using ferrite shielding. It can help inform the development of future WPT technologies. The result obtained through simulation, i.e., coil-to-coil efficiency, is 98.88 to 99.7360% at 6.78MHz frequency for a 5-mm- to 50-mm-thick ferrite rectangular coupler using ANSYS Maxwell and ANSYS simplorer software.